1996
DOI: 10.1107/s0108768196009639
|View full text |Cite
|
Sign up to set email alerts
|

Structural relationship of various squarates

Abstract: This work illustrates the structural relationship between three types of metal squarates as well as the ligand in its acid form and in its monoanion salt. Squaric acid, H2C404, is known to have a polymeric layer structure with planar molecules connected through intermolecular hydrogen bonds. The interlayer distance is only 2.649A. The crystal of H2NMe2[H3(C404)2] is found to contain columns of [H3(C404)2-] repeating units, again connected by intermolecular hydrogen bonds. Within the repeated unit, there is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…Two Cd ions are linked together through two bridging water molecules to form a [Cd(dpa)(H 2 O)] 2 4+ dimeric fragment (see Figure 5 [a] bonds fall in the same range, analogous to those in the [Cd(C 4 O 4 )(H 2 O) 2 ] complex. [10] The Cd···Cd separations along the µ 2 -O water and µ 1,2 -C 4 O 4 2-bridges are 3.670(1) and 7.672(1) Å, respectively. It should be noted that adjacent ladders are displaced by half a repeating unit along the a and c axes.…”
Section: Crystal Structures Of [Cd(c 4 O 4 )(Dpa)(h 2 O)] (2)mentioning
confidence: 99%
See 3 more Smart Citations
“…Two Cd ions are linked together through two bridging water molecules to form a [Cd(dpa)(H 2 O)] 2 4+ dimeric fragment (see Figure 5 [a] bonds fall in the same range, analogous to those in the [Cd(C 4 O 4 )(H 2 O) 2 ] complex. [10] The Cd···Cd separations along the µ 2 -O water and µ 1,2 -C 4 O 4 2-bridges are 3.670(1) and 7.672(1) Å, respectively. It should be noted that adjacent ladders are displaced by half a repeating unit along the a and c axes.…”
Section: Crystal Structures Of [Cd(c 4 O 4 )(Dpa)(h 2 O)] (2)mentioning
confidence: 99%
“…The second one (C5-C8) also adopts a µ 1,2,3 -bridging mode [12] to link Cd(1) with Cd(3) (5.918 [a] Cd (1) (14) ii 82.42 (9) O ( and 6.057 Å) and Cd(1) with Cd(1) (8.434 Å), respectively. The last one (C9-C10) adopts a µ 1,2,3,4 -bridging mode [10] ( Figure 2) to link Cd(2) with Cd(3) (2 × 5.854 and 2 × 6.088 Å), Cd(2) with Cd(2) (8.434 Å) and Cd(3)···Cd(3) (8.457 Å), respectively. To the best of our knowledge, compound 1 is the first coordination framework consisting of a Cd/squarate system with hybrid µ 1,2,3 -and µ 1,2,3,4 -bridging modes of squarates.…”
Section: Synthesis and Ir Spectroscopy Of Compounds 1 Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Squarate acts as a bridge between two or more metal atoms in mono-or polydentate coordination modes when acting as a ligand towards first row transition metal ions [8,9]. It coordinates to Fe(II), Fe(III), Ni(II) and Cu(II) complexes in a l-1,3 fashion, giving binuclear [10][11][12] and chain structures [13,14], whereas the l-1,2 coordination mode has been reported for binuclear and chain complexes of Cu(II) and Pd(II) [15,16]. It is also observed that the squarate anion, with Cu(II) and Ni(II), acts as a tetramonodentate ligand and forms polynuclear compounds [17].…”
Section: Introductionmentioning
confidence: 99%